Learning About Culture Through Media Peripherals: A Case Study on "Molly of Denali" - Liu, Claire J. (Tufts Archival Research Center, 2021)
This thesis is a case study on the media peripherals (podcast, social media, offline games, online games) of PBS show "Molly of Denali". It aims to look at how media peripherals can be inclusive and diverse and how other media brands can learn from "Molly of Denali".; Advisor: Julie Dobrow, Ph.D.